(3MSH GdfXGe GdeGdj GdeMGSHj (BSCF (IAS/IFRS( : (3OQhS , ehGVjY h eSGFd eMdhdIs - (3UdGM(B, (3MhGSs ((3GdLRGFQ(B:s (3OGQ YHO GddWja(B,s, 2014)
(3CSS h eHGOF GdeMGSHI GdeGdjI, GdeHGOF h GdaQVjGJ h GdNUGFU GdeMGSHjI , GdCSS h GdNUGFU GdeMGSHjI , GdeTQhY GdJegjOj ddfXGe GdeGdj GdeMGSHj GdLOjO (BSCF (3, GdJOabGJ , GdejRGfjI GdeMGSHjI , GdOaGJQ GdeMGSHjI h GdOhQI GdeMGSHjI , OaJQ GdjhejI , ejRGf GeQGLYI , OQGSI GdMSGHGJ GdeOhfI , GdGMJjGWGJ h GdJNajVGJ h GdahJQI h GdZdGaGJ h GdeQOhOGJ h GdGgJdGcGJ h CNjQG GdJfGRd Yf GdJKHjJGJ h NSGQI GdbjeI(B.s
(3eQGLY U(B.206s
Keywords: (3GdeMGSHI GdJMdjdjIs